Aunty’s English lesson / Prof. Madya Dr. Soo Kum Yoke - Soo, Kum Yoke (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
Aiyah! Your English no good ah? Don’t worry, no pain, no gain… Come, Aunty teach you…